A cluster randomized controlled trial of brief follow-up practice sessions on intervention maintenance. (October 2021) - Nelson, Peter M.; Klingbeil, David A.; Van Norman, Ethan R.; Parker, David C.
Abstract: Despite considerable knowledge of the factors that influence initial intervention response, little is known about how to sustain successful intervention response over time. The current study examined spring literacy outcomes for kindergarten ( n  = 177), second ( n  = 149), and third grade students ( n  = 204) who successfully exited an evidence-based tutoring program during the fall semester. Successful responders in kindergarten, second, and third grade were randomly assigned by school to receive either no follow-up support or access to a once-weekly oral practice session. Results were mixed across grades and outcomes, but in kindergarten and third grade, treatment corresponded to an approximately 15% increased likelihood of meeting year-end benchmarks on targeted literacy skills. Findings are discussed in the context of suggestions for higher-quality longitudinal research designs of educational interventions.